History Education in the Anthropocene - McGregor, Heather E.; Karn, Sara; Pind, Jackson (Journal of the Canadian Association for Curriculum Studies, 2020)
As much as history education is supposed to be about the past, it is oriented towards the future. History teachers are guided by a variety of purposes, such as cultural inheritance, critical and disciplinary thinking, identity formation and personal development, or activism and social change. Each of these purposes is imbued with particular notions of memory, citizenship and other values relevant to preparing young people for the future. While it may not always be explicit, a prevailing assumption in history education, as with Canadian curriculum, generally speaking, is that the future is a place and time to which we should look forward, as it will improve upon the past. But as we are coming to know, that may not be a responsible or accurate frame to pass on to the next generation. What theoretical and practical supports can help history educators renew their teaching in light of the Anthropocene, and particularly the climate crisis? In seeking to attune history education to a relational, ecological and ethical future orientation, we turned to the fields of Indigenous studies, environmental history and climate change education. We suggest some new, and even radical, directions we might look as a community of history educators. In doing so, we hope to nurture solidarity in navigating uncertainty together. With a set of common questions, assumptions and goals to guide us, we may find ways of teaching and learning that respond more meaningfully to the precarity of our times.